The Presence and Importance of Beauty in the Byzantine Epigrams About the Cross and the Crucifixion of Jesus Christ: Some Basic Observations - Kantaras, Anastasios (Acta Classica Universitatis Scientiarum Debreceniensis, 2021)
Scholar poetry, particularly the epigram, has been a literary means of expression not only of ideas and attitudes about life but also of religious sentiment and profound religious faith. Delving into the epigrams of the second category, particularly those related to the Cross and the Crucifixion, our attention will be focused on the presence of beauty, its meaning, and the role it played within the category of Byzantine epigrams. The aim of this article is to identify relevant epigrams (by anonymous or known writers), make some basic observations and reach certain conclusions regarding the issue of beauty.